Theory of induced magnetic moments and x-ray magnetic circular dichroism in Co-Pt multilayers - EDERER, CLAUDE (American Physical Society, 2002)
For Co-Pt multilayers, the magnetic moments of the Pt atoms and the x-ray magnetic circular dichroism (XMCD) spectra at the L2 and L3 edge of Pt are calculated-by the ab initio density-functional electron theory. The calculated magnetization profile for an ideal Co-Pt interface is in part different from the profile obtained by x-ray resonant magnetic reflectometry for the real interface. Some of the assumptions that are commonly adopted to determine the magnetic moments from the XMCD spectra via the sum rules are critically assessed for the Co-Pt system. It is shown that the orbital sum rule is strongly violated near the Co-Pt interface whereas the spin sum rule is approximately fulfilled provided the magnetic dipole term (Tz) is included in the analysis.
PUBLISHED
Keywords: Physics